Design of a polarization‐insensitive three dimensional microwave absorber for ultra‐wideband RCS reduction. Issue 4 (1st February 2022) - Li, Liang; Zhang, Binchao; Jin, Cheng; Lv, Qihao; Yin, Liyuan; Zhang, Pengyu; Tian, Buning
Abstract: A polarization‐insensitive three‐dimensional (3‐D) microwave absorber is proposed in this letter for ultra‐wideband radar section cross (RCS) reduction. The lossy layer of the designed absorber is evolved from the bent metallic strip with a center‐embedded resistor, which performs the property of absorption‐reflection‐absorption due to its multimode resonances. A short stub with a center‐embedded resistor is connected to the long‐bent strip to abolish the reflection performance, for the sake of achieving wide absorption performance. The fundamental working principle of the designed structure is explained adequately using an intuitive equivalent circuit model. Additionally, the absorber is designed, fabricated, and measured for validation, whose fractional bandwidths is 151.5% with at least 10‐dB RCS reduction.